2012
DOI: 10.1590/s1020-49892012001000010
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of studies comparing 24-hour and spot urine collections for estimating population salt intake

Abstract: There is great interest in replacing 24-h urine Na with easier methods to assess dietary Na. However, whether alternative methods are reliable remains uncertain. More research, including the use of an appropriate study design and statistical testing, is required to determine the usefulness of alternative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
148
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(163 citation statements)
references
References 27 publications
13
148
1
1
Order By: Relevance
“…Our data showed that the salt consumption estimated by the gold-standard is higher in comparison to other populations 9,21,25 , being higher than twice the current recommendation of 5 g of salt a day 29 . The impact of salt consumption on blood pressure of the study participants was described in another publication 30 .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our data showed that the salt consumption estimated by the gold-standard is higher in comparison to other populations 9,21,25 , being higher than twice the current recommendation of 5 g of salt a day 29 . The impact of salt consumption on blood pressure of the study participants was described in another publication 30 .…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, there have been eff orts to standardize more practical methods of collection 8,10,21 . The accuracy of these methods, however, has been questioned [21][22][23][24] , and that is why it is necessary to conduct validation studies in diff erent populations than that they were developed [11][12][13]25 . The accuracy of the estimation of sodium excretion in casual urine mostly depends on the estimated accuracy of the 24-hour creatinine excretion, based on gender, weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the correlations are in the range of 0·50 to 0·80 as hypothesized (16) . The observed β coefficients of 0·53 and 0·54 for spot urine Na and K, respectively, are higher than the β of 0·34 for spot urine Na that Brown and colleagues found in women (15) .…”
Section: Discussionsupporting
confidence: 52%
“…Studies have shown good correlations between Na:creatinine and K:creatinine in spot urine and respective ratios in 24 h urine (12,14,16) . In addition, Brown and colleagues showed that β coefficients derived from regression analyses of spot urine samples v. 24 h urinary Na excretions can be used to predict 24 h excretions with reasonable accuracy (15) .…”
mentioning
confidence: 99%
“…Furthermore, it is difficult to accurately infer the absolute excretion of biomarkers with the use of spot urine samples even after adjustment for dilution with the use of the urinary creatinine concentration, which is also subject to within-person variability (5,6) and is influenced by individuals' meat intakes (4). Therefore, in epidemiologic studies, 24-h urine samples are preferred over spot urine samples to reduce the extraneous variability of biomarkers that is due to the timing of sample collection and very short-term changes in exposures (4,7). This may largely explain the contradicting observations regarding sodium excretion in relation to cardiovascular disease shown in 2 recent studies that used spot urine samples (8) compared with 24-h urine samples (9) to assess longterm sodium intake.…”
Section: Introductionmentioning
confidence: 99%